Implicações psicossociais da violência nos modos de vida de prostitutas pobres - Silva, Lorena Brito da (2014)
This dissertation is result of the interest on studying female prostitution and violence, two polysemic and complex phenomena. Specifically, this relationship is being discussed in the context of low prostitution or low meretricious, which is characterized by a dialectical relationship between the experience of prostitution and the context of the street, powering a series of vulnerabilities and ways of socializing. The violence reflects the historical and private logic of silencing and reproduction although it occurs in public space, not existing specifically, as regards to violence against prostitutes, representatives informations on the country. The ways of life are a privileged scenario to study the psychosocial implications of violence, for revealing the symbolic and material conditions of production of subjectivities, of organization of life and relationships in areas of prostitution. In view of these issues, the research question arises as to the psychosocial implications of violence impact the way of life of prostitutes in situations of poverty? The general objective of the study is to understand the psychosocial implications of violence in the way of life for poor prostitutes. The specific objectives are: Describe the lifestyles of women exercising the low prostitution; Understand the meanings constructed on violence; Analyze ways to deal with violence built by prostitutes. The research is qualitative and has been developed with 7 women who live in Barra do Ceara, a neighbourhood in Fortaleza. The investigation had an ethnographic perspective, having performed as methodological procedures and data construction, participant observation, dialogical visit, the individual interview and the technique of generating objects. For data analysis was performed the Qualitative Analysis of Bardin, with the assistance of ATLAS.ti 5.2 software. The 57 analysis categories were organized into three broad categories entitled of "Ways of life of poor prostitutes", "Meanings about violence in prostitution", "Psychosocial expressions of violence in the way of life”. As main results, we notice that the dynamics of the low prostitution is engineered with the territorial dynamics, with the codes and rules of the prostitution area in constant dispute and agreement with the community. The violence is a relational web that seeks to prevent the recognition of the other (class, gender or ethnicity) using physical or symbolic force, undermining the possibilities of dialogue, on one hand, and creating other codes, forms of social interaction and performances, on the other. As main forms of facing are: analysis of the profile of the customer and the conditions for implementing the program, establishment a routine and a personal organization of work, participation in religious groups, partnership with specific bars or home, maintaining ties of partnership in the zone of prostitution.